Design of monitoring system for controlling the Temperature of chicken coops based on Internet of Things by utilizing Thingspeak: - Sarah Azzahra; Andi Tri Setyohadi; Lela Mariya; Budi Wibowo; Andrie Yuswanto (Jurnal Komputer dan Elektro Sains, 2023)
Broiler chickens are cattle whose growth is affected by ambient temperature. Inappropriate chicken cage temperatures can affect productivity and cause death in broiler chicken, so setting the cage temperature should be done. The design of this automatic temperature control system used the ESP32 microcontroller as the primary controller, the DHT22 as the enclosure temperature sensor and the ThingSpeak as remote monitoring. The microcontroller shall order if the measured temperature is above the set temperature limit and shall order the LED to light red, if the measured temperature is below the specified temperature limit to light blue, but due to the limitations of the author's LED material uses yellow. The results of the study showed that this automatic chicken coop temperature setting tool can work well to automatically regulate the chicken coop temperature and that the data on the results of this study would be entered into ThingSpeak and printed on the LCD.